The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3324/haematol.2016.159517
|View full text |Cite
|
Sign up to set email alerts
|

Acute lymphoblastic leukemia cells create a leukemic niche without affecting the CXCR4/CXCL12 axis

Abstract: BdR and RP contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…vivo co-cultures of primary mesenchymal stromal cells and either the Nalm6 cell line or primary ALL cells that although the CXCL12/CXCR4 axis was involved in leukemic cell migration, other chemokines, such as C-C motif chemokine ligand 2 (CCL2) and CXCL8 may be involved in leukemic niche formation, independently of the CXCL12/CXCR4 axis.Transwell assays also demonstrated that leukemic cells could recruit mesenchymal stromal cells to initiate the leukemic niche, in which secreted chemokines might attract other leukemic cells while inhibiting that of healthy hematopoietic progenitors and mesenchymal stromal cells[201]. These results are consistent with those of other studies including that of Colmone et al in which Nalm6 cells colonized CXCL12 niches in the BM of xenografted mice, which subsequently resulted in marked downregulation[43,202].…”
supporting
confidence: 89%
“…vivo co-cultures of primary mesenchymal stromal cells and either the Nalm6 cell line or primary ALL cells that although the CXCL12/CXCR4 axis was involved in leukemic cell migration, other chemokines, such as C-C motif chemokine ligand 2 (CCL2) and CXCL8 may be involved in leukemic niche formation, independently of the CXCL12/CXCR4 axis.Transwell assays also demonstrated that leukemic cells could recruit mesenchymal stromal cells to initiate the leukemic niche, in which secreted chemokines might attract other leukemic cells while inhibiting that of healthy hematopoietic progenitors and mesenchymal stromal cells[201]. These results are consistent with those of other studies including that of Colmone et al in which Nalm6 cells colonized CXCL12 niches in the BM of xenografted mice, which subsequently resulted in marked downregulation[43,202].…”
supporting
confidence: 89%
“…CXCR2 primarily mediates neutrophil migration to sites of inflammation (Richardson et al, 2003); in addition, it represents a selective migratory pathway for BCP-ALL blasts toward the leukemic niche (De Rooij et al, 2017). Since we previously showed that E/R altered cell migration (Palmi et al, 2014) E/R + =30Á2 AE 9Á1; ctr = 14Á3 AE 9Á6, P < 0Á01).…”
Section: The Inflamed Mesenchymal Niche Preferentially Attracts E/r + B-progenitors Through the Cxcr2 Receptormentioning
confidence: 96%
“…Of note, we have previously suggested that may affect pre-leukemic cells interactions with the BM stroma by altering their adhesive and migratory properties (Palmi et al, 2014). In addition to function as important modulators of inflammation (Bernardo & Fibbe, 2013), BM-mesenchymal stromal cells (MSC) have gained great interest for their active role in leukemia pathogenesis (Lo et al, 2014;Polak et al, 2015;Naderi et al, 2015;De Rooij et al, 2017). In particular, it has been shown that BM-MSC alterations are able to induce genotoxic stress in HSPC leading to hematological malignancies (Raaijmakers et al, 2010;Zambetti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These alterations are not restricted to malignancies in myeloid lineage. Ex vivo coculture model has indicated that acute lymphoblastic leukaemia cells can create a leukaemic niche in the direction of attracting leukaemic cells and repelling normal haematopoietic cells 7 . BM‐MSCs from multiple myeloma (MM) patients also show much lower proliferative activity and different gene expression compared with normal BM‐MSCs 8 .…”
Section: Introductionmentioning
confidence: 99%